Second language acquisition at the interfaces - White, Lydia (Lingua, 2011)
In recent research on L2 acquisition, there has been considerable emphasis on interfaces between the linguistic system and grammar external components, such as syntax/discourse, or between different modules of grammar, such as syntax/semantics, syntax/morphology or morphology/phonology. This has led to proposals that difficulties experienced by L2 learners can be explained in terms of problems with integrating linguistic phenomena relevant to certain interfaces. With some exceptions, there has been a tendency to consider at least some interface phenomena as inherently problematic, while others are inherently unproblematic. This paper provides an overview of L2 research on interfaces, comparing different interface domains. I conclude that we must be wary of assuming that all linguistic interfaces are equally problematic or unproblematic or that different linguistic phenomena pertaining to the same interface will necessarily behave alike.